2019
DOI: 10.1111/crj.13103
|View full text |Cite
|
Sign up to set email alerts
|

The value of flexible bronchoscopy in pulmonary infections of immunosuppressed children

Abstract: Objectives:To demonstrate the value of flexible bronchoscopy (FB) and bronchoalveolar lavage (BAL) when determining causes of lung infection in immunocompromised children; to investigate differences in causes and radiological features of lung infections following bone marrow transplantation (BMT) compared to other immunosuppressive conditions; to evaluate the reliability of radiological findings when predicting the pathogen. Methods: We retrospectively evaluated 132 immunosuppressed children who underwent FB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…39 A study of FB and BAL in immunosuppressed children found the procedure to be diagnostic in 65.1% patients and the antimicrobial treatment changed for 56.8% patients. 40 Furthermore, FB was found to have contributed to a specific diagnosis in almost 89.8% of children with congenital cardiac disease for evaluation of pulmonary disease, 41 and lead to a specific diagnosis in 33% of children who had bronchoscopic evaluation for unexplained recurrent and persistent pneumonia. 42 In another retrospective review consisting of 149 children, FB was described as a crucial diagnostic (confirming, ruling out and discovering unexpected diagnosis) and therapeutic tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 A study of FB and BAL in immunosuppressed children found the procedure to be diagnostic in 65.1% patients and the antimicrobial treatment changed for 56.8% patients. 40 Furthermore, FB was found to have contributed to a specific diagnosis in almost 89.8% of children with congenital cardiac disease for evaluation of pulmonary disease, 41 and lead to a specific diagnosis in 33% of children who had bronchoscopic evaluation for unexplained recurrent and persistent pneumonia. 42 In another retrospective review consisting of 149 children, FB was described as a crucial diagnostic (confirming, ruling out and discovering unexpected diagnosis) and therapeutic tool.…”
Section: Discussionmentioning
confidence: 99%
“…One study found it useful in immunocompetent children with unexplained infiltrates on chest radiographs where a specific diagnosis was made in 30% of patients 39 . A study of FB and BAL in immunosuppressed children found the procedure to be diagnostic in 65.1% patients and the antimicrobial treatment changed for 56.8% patients 40 . Furthermore, FB was found to have contributed to a specific diagnosis in almost 89.8% of children with congenital cardiac disease for evaluation of pulmonary disease, 41 and lead to a specific diagnosis in 33% of children who had bronchoscopic evaluation for unexplained recurrent and persistent pneumonia 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment should be initiated immediately after obtaining appropriate samples, that is, nasopharyngeal aspirates in infants [132], sputum in adolescents, and BAL with fiberoptic bronchoscopy in children of all ages [66]. Fiberoptic bronchoscopy is generally a safe and highly diagnostic procedure in the immunocompromised host with pneumonia due to opportunistic pathogens [133].…”
Section: Treatment Of Pjpmentioning
confidence: 99%
“… 13 FB and BAL are useful in immunocompetent children with unexplained infiltrates on chest radiographs leading to specific diagnosis in 30% of patients, 14 as well as immunosuppressed children (diagnostic in 65.1% of patients and the antimicrobial treatment changed for 56.8%of patients). 15 Furthermore, a specific diagnosis was made in almost 89.8% of children with congenital cardiac disease 16 and 33% of children with unexplained recurrent and persistent pneumonia, 17 after bronchoscopic evaluation. In another retrospective review consisting of 149 children, FB was described as a crucial diagnostic (confirming, ruling out and discovering unexpected diagnosis) and therapeutic tool.…”
Section: Introductionmentioning
confidence: 99%